The classifications of quaternionic osculating curves in Q4 - Yilmaz, Munevver Yildirim; Kulahci, Mihriban (Walter de Gruyter Gmbh, 2018)
In this work, we define a quaternionic osculating curves and give the conditions for curves to be osculating with the help of curvature functions.
Keywords: Real quaternion; osculating curve; curvature function; Frenet equations